1968 : on the edge of world revolution - Gassert, Philipp; Klimke, Martin (Black Rose Books, 2018)
"Released for the fiftieth anniversary of that momentous year, Philipp Gassert's and Martin Klimke's seminal 1968 presents a wide-ranging survey. Short chapters, written by local eyewitnesses and historical experts, cover events in thirty-nine countries to give a truly global view. Photographs throughout the book illustrate the drama of events described in each chapter. It includes the transcript of a panel discussion organized for the fortieth anniversary, with eyewitness testimony from Norman Birnbaum, Patty Lee Parmalee, and Tom Hayden. Originally released as a bulletin of the German Historical Institute, it is being published in book form for the very first time and includes a new foreword by Dimitri Roussopoulos, a veteran activist involved on an international level in the tumult of the 1960s."--